Business Feasibility Study Analysis on Marketing Strategy of Maha Karya Madurasa Bread Factory in Tanah Merah Bangkalan - Nur Ina Avia; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
This research aims to analyze the business feasibility of the marketing strategy of the Maha Karya Madurasa Bread Business Factory in Tanah Merah Bangkalan. The research method used is descriptive with a qualitative approach. Primary data was obtained through interviews and observations, while secondary data was obtained from literature studies and related documents. The research results show that the Maha Karya Madurusa Bread Factory has a fairly good marketing strategy. The marketing strategy includes determining prices, products, promotions and sales places that suit the target market. This factory also has competitive advantages compared to other competitors, namely quality products, affordable prices and good service. Based on the results of this research, it can be concluded that the Maha Karya Madurasa Bread Business Factory has a good marketing strategy and good business feasibility. Therefore, companies need to continue to improve their marketing strategies and maintain the quality of their products in order to compete in an increasingly competitive market.